Pelaksanaan Kegiatan Ekstrakurikuler Sar Pelajar SFAT Dalam Konteks Penanggulangan Bencana Di SMK Al-Mabrur Kabupaten Banjarnegara - Irega Gelly Gera; Arif Budi Wurianto; Abdul Kadir Raharjanto (Jurnal Kebijakan dan Pengembangan Pendidikan, 2016)
Abstract: The purpose of this research is to find out the implementation of SFAT Student SAR extracurricular in the context of disaster management in SMK Al-Mabrur, Banjarnegara Regency. The research method used in this study is descriptive qualitative. The location of the study was at SMK Al-Mabrur, Pejawaran District, Banjarnegara Regency. The subjects of this study were the deputy headmaster in the student field, extracurricular coaches, and students. Data collection techniques using interviews, observation, and documentation. Data analysis techniques using the interactive model of Miles and Huberman 1994, and testing the validity of the data using triangulation of sources and techniques. The results of the study showed that the implementation of SFAT Student SAR extracurricular activities in the context of disaster management in SMK Al-Mabrur Banjarnegara District was seen through three factors, namely the agenda of the SAR SAR SFAT activities which included registration, weekly routine training, education and education, materials for the SFAT Student SAR activities. which contains disaster and SAR material, the instructor's method is divided into three, namely a few lectures, an emphasis on practice, and a semi-military situation. The driving factor consists of the selection of competent coaches, interesting activities and high enthusiasm, and support from the school principal. Factors that have hindered the SFAT Student SAR activities are the lack of funds for facilities and infrastructure, the and post-processing of activities began to be less effective.Keywords: Extracurricular, SAR, Disaster Abstrak: Penelitian bertujuan mengetahui pelaksanaan ekstrakurikuler SAR Pelajar SFAT dalam konteks penanggulangan bencana di SMK Al-Mabrur Kabupaten Banjarnegara. Matode penelitian yang digunakan dalam penelitian ini adalah deskriptif kualitatif. Lokasi penelitian bertempat di SMK Al-Mabrur Kecamatan Pejawaran Kabupaten Banjarnegara. Subjek penelitian ini adalah wakil kepala sekolah bidang kesiswaan, guru pembina ekstrakurikuler, dan siswa. Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Teknik analisis data menggunakan model interaktif Miles and Hubberman 1994, dan uji keabsahan data menggunakan trianggulasi sumber dan teknik. Hasil penelitian yang menunjukkan bahwa pelaksanaan kegiatan ekstrakurikuler SAR Pelajar SFAT dalam konteks penanggulangan bencana di SMK Al-Mabrur Kabupaten Banjarnegara dilihat melalui tiga faktor yaitu agenda kegiatan SAR Pelajar SFAT yang berisi kegiatan pendaftran, pelatihan rutin mingguan, diklat dan pengorenan, materi kegiatan SAR Pelajar SFAT yang berisi materi kebencanaan dan SAR, cara mengajar pembina yang terbagi tiga yaitu sedikit ceramah, penekan pada praktek, dan mengkondisikan situasi semi militer. Faktor pendorong terdiri dari pemilihan pembina yang berkompeten, kegiatan yang menarik dan antusiame yang tinggi, dan dukungan dari kepala sekolah. Faktor yang menjadi penghambat kegiatan SAR Pelajar SFAT adalah kurangnya dana sarana dan prasarana, dan pasca pengorenan kegiatan mulai kurang efektif.Kata kunci: Esktakurikuler, SAR, Bencana